The role of the geographical proximity and the quality of academic research to university-industry linkages - Renato Garcia; Veneziano Araújo; Suelene Mascarini; Emerson Santos; Ariana Costa (European Regional Science Association (ERSA), 2013)
This paper examines how the geographical proximity of university-industry linkages relates to the quality of an institution?s research, local efforts in research and development (R&D), and characteristics of a region?s production structure. The important role of universities for the firms? innovative efforts has been widely accepted in the literature. In particular, universities serve as a source of new scientific and technological knowledge and geographical proximity can facilitate an interactive learning process between universities and industry. To exam this point, database of the Brazilian Ministry of Science and Technology was used, such it collects and compiles information on the activities of research groups in Brazil and their interactions with firms. Findings from this study show a positive correlation between the quality of research groups and the mean distance of interactions with firms. Top-tier research groups interact with both local firms (due to the convenience of being co-located) and more distant producers in need of cutting edge research and expertise to support advanced innovation. It is evident, then, that the costs of establishing long-distance university-industry relationships are overcome by the benefits offered by interacting with high capabilities research groups to solve complex and highly specific problems. Results also show that the increasing positive correlation between academic quality and interaction distance decreases with an increase in quality. This pattern was demonstrated by the quadratic parameter used in the empirical model and is particularly significant when top-tier research groups are involved. Thus, the mean distance of interactions tends to decrease when the interactions involve centres of academic excellence. However, the importance of second-tier universities cannot be neglected. Results from the empirical model indicate a positive correlation between academic research quality and interaction distance, suggesting that second-tier universities tend to interact more frequently with local firms. Findings from this study indicate that second-tier universities are well-equipped to handle the simpler needs of local producers, which do not require cutting edge expertise or complex academic capabilities. Findings from this study have important policy implications. Results emphasise the importance of creating and supporting top-tier centres of advanced research, since these centres are able to generate and exchange complex knowledge through university-industry linkages. It is also important to support research development in second-tier universities, as these universities attend to the specific needs of local businesses and help enhance their competitiveness. Finally, it is worth noting that industry R&D efforts greatly contribute to the development of university-industry linkages.
Keywords: R12; O18; O31; 330